Heterologous Expression and Auto-Activation of Human Pro-Inflammatory Caspase-1 in Saccharomyces cerevisiae and Comparison to Caspase-8 - Valenti, Marta; Molina, María; Cid, Víctor J. (Frontiers in Immunology, 2021)
Caspases are a family of cysteine proteases that play an essential role in inflammation, apoptosis, cell death, and development. Here we delve into the effects caused by heterologous expression of human Caspase-1 in the yeast Saccharomyces cerevisiae and compare them to those of Caspase-8. Overexpression of both caspases in the heterologous model led to their activation, and caused mitochondrial hyperpolarization, ROS production, damage to different organelles, and cell death. All these effects were dependent on their protease activity, and Caspase-8 was more aggressive than Caspase-1. Growth arrest could be at least partially explained by dysfunction of the actin cytoskeleton as a consequence of the processing of the yeast Bni1 formin, which we identify here as a likely direct substrate of both caspases. Through the modulation of the GAL1 promoter by using different galactose:glucose ratios in the culture medium, we have established a scenario in which Caspase-1 is sufficiently expressed to become activated while yeast growth is not impaired. Finally, we used the yeast model to explore the role of death-fold domains (DD) of both caspases in their activity. Peculiarly, the DDs of either caspase showed an opposite involvement in its intrinsic activity, as the deletion of the caspase activation and recruitment domain (CARD) of Caspase-1 enhanced its activity, while the deletion of the death effector domain (DED) of Caspase-8 diminished it. We show that Caspase-1 is able to efficiently process its target gasdermin D (GSDMD) when co-expressed in yeast. In sum, we propose that S. cerevisiae provides a manageable tool to explore Caspase-1 activity and structure-function relationships.